Carrageenan hard capsules reinforced with cellulose nanocrystals dissolved in deep eutectic solvent and hydroxypropyl methylcellulose - Okwuwa, Chigozie Charity; Fatmawati, Adam; Ries, Michael E.; Farhan, Mohd Said; Olunusi, Samuel Olugbenga (International Association of Dietetic Nutrition and Safety (IADNS), 2025)
Carrageenan-based biocomposites are promising materials due to their biodegradability, cost-effectiveness and wide availability, making them suitable for food and drug delivery applications. This study addresses the brittle nature of refined carrageenan by reinforcing it with cellulose nanocrystal (CNC) dissolved in choline chloride lactic acid-based deep eutectic solvent (DES) and comparing the mechanical performance of formulations with and without hydroxypropyl methylcellulose (HPMC). Four formulations were developed: 3WH (3-g carrageenan with HPMC), 3WOH (3 g without HPMC), 5WH (5 g with HPMC) and 5WOH (5 g without HPMC). The 5WH formulation demonstrated superior mechanical properties, including a tensile strength of 89.37 MPa, a capsule loop strength of 49.33 MPa and a viscosity of 1217.00 mPas−1, which indicated excellent mechanical performance and structural integrity. Molecular modelling using Gaussian software was conducted to investigate the interactions between CNC and DES, revealing an interaction energy of 1995 kJ/mol and an enthalpy of formation of −3123.75 kJ/mol. The bond distance between DES components was observed as 2.48 and 1.98 Å, with angles changing from 23.5° to 128° upon dissolution. The disappearance of peaks in the 1H nuclear magnetic resonance spectra evidenced this. These findings offer valuable insights into the molecular interactions in cellulose dissolution and pave the way for innovative plant-based hard capsules for industrial applications.